Pengaruh Struktur Modal, Likuiditas, dan Operating Efficiency Ratio terhadap Kinerja Keuangan - Vina Ayu Naafilah; Ratna Anggraini; Surya Anugrah (LPPM Universitas Negeri Jakarta, 2026)
The financial performance of transportation and logistics companies is affected by capital structure, liquidity, and operational efficiency. This study aims to analyze the influence of these variables on the financial performance of transportation and logistics companies listed on the Indonesia Stock Exchange from 2018 to 2024. Return on Assets (ROA) is used to measure financial performance, while the Debt to Equity Ratio (DER), Current Ratio (CR), and Operating Efficiency Ratio (BOPO) represent capital structure, liquidity, and operational efficiency, respectively. A quantitative research design was applied using secondary data collected from annual financial statements. The sample consisted of 90 firm-year observations, which were analyzed using panel data regression with EViews 13. The results show that capital structure and liquidity positively and significantly affect financial performance, whereas operational efficiency has a significant negative effect. Therefore, effective debt management, sufficient liquidity, and improved cost efficiency are essential for strengthening profitability and achieving sustainable financial performance.